High-dimensional mass cytometry reveals systemic and local immune signatures in necrotizing enterocolitis - Liu, Yufeng; Zhou, Jialiang; Chen, Baozhu; Liu, Xiao; Cai, Yao; Liu, Wei; Hao, Hu; Li, Sitao (Frontiers in Immunology, 2023)
Objective: Patients with necrotizing enterocolitis display severe gastrointestinal complications, but the mechanism driving this clinical profile remains unknown. We used mass cytometry time-of-flight to characterize and compare immune cell populations in the blood and intestinal tissue from patients with and without (controls) necrotizing enterocolitis at single-cell resolution. Methods: We completed a deep mapping of the immune system of the peripheral blood mononuclear cells and intestinal mucosa tissue using mass cytometry to evaluate immune cell types, which revealed global immune dysregulation characteristics underlying necrotizing enterocolitis. Results: Compared with controls, natural killer cells display signs of heightened activation and increased cytotoxic potential in the peripheral blood and mucosa of patients with necrotizing enterocolitis. Furthermore, CD4+ T effector memory cells, non-classical monocytes, active dendritic cells, and neutrophils were specifically enriched in the mucosa, suggesting trafficking from the periphery to areas of inflammation. Moreover, we mapped the systemic and local distinct immune signatures suggesting patterns of cell localization in necrotizing enterocolitis. Conclusions: Patients with NEC display global immune dysregulation, such as the signs of heightened activation of NK and CD8+ T cells and increased cytotoxic potential. The circulating B cell compartment of NEC patients is skewed towards plasmablasts, and myeloid cell homeostasis is disrupted. This information might be used to develop precise diagnosis and therapies that target specific cell populations in patients with necrotizing enterocolitis.